Pengaruh Lokasi Zeolit Alam Bayah terhadap Adsorpsi Amonium: Studi Kinetika dan Kesetimbangan - Hakiki, Muhammad; Makiyi, Muhammad; Nuryoto, Nuryoto; Rahmayetty, Rahmayetty; Kustiningsih, Indar; Kurniawan, Teguh (Jurnal Teknologi Lingkungan, 2021)
ABSTRACT Household waste is one of the most significant contributors to wastewater that can pollute the environment, one of which is ammonium pollution. Ammonium pollution can be reduced by natural zeolite by using the adsorption method. This research aims to utilize natural zeolite as an adsorbent that can reduce ammonium levels in wastewater, determine which natural zeolite has the most significant adsorption power from 4 locations, determine natural zeolite characterization of Bayah. This study is also to create a model equilibrium equations and reaction kinetics from the adsorption method. The method used is the adsorption method, X-ray diffraction (XRD), Scanning Electron Microscope (SEM), and Brunauer-Emmett-Teller (BET). This study's results were that natural zeolites location 4 could adsorb 99.25% of ammonium and showed the highest adsorption capacity of ammonium. Characterization using XRD analysis obtained the types of zeolite mordenite, clinoptilolite, quartz, and heulandite. The surface area of Bayah natural zeolite in the 4th location is 46 m2/g. The suitable equilibrium model for the adsorption of ammonium by natural zeolites is the Freundlich model. The most suitable adsorption kinetics model for the adsorption of ammonium by Bayah natural zeolites is the pseudo-first-order model. Keywords: household waste, ammonium, eutrophication, natural zeolites   ABSTRAK Limbah rumah tangga adalah salah satu penyumbang limbah cair terbesar yang dapat mencemari lingkungan salah satunya pencemaran amonium. Pencemaran amonium dapat dikurangi dengan zeolit alam dengan menggunakan metode adsorpsi. Tujuan dari penelitian ini adalah menentukan zeolit alam yang memiliki daya adsorpsi terbesar dari 4 lokasi berbeda, melakukan karakterisasi zeolit alam Bayah, dan memodelkan persamaan kesetimbangan dan kinetika reaksi adsorpsi amonium. Karakterisasi zeolit dilakukan dengan analisis X-ray diffraction (XRD), Scanning Electron Microsope (SEM), dan luas permukaan material menggunakan model Brunauer-Emmett-Teller (BET). Hasil dari penelitian ini adalah zeolit alam lokasi 4 memiliki  kapasitas adsorpsi amonium paling besar, yaitu 9,25%. Adapun kapasitas adsorpsi amonium yang paling besar ditunjukkan oleh zeolit alam Bayah lokasi 4. Analisis XRD menunjukkan bahwa seluruh zeolit Bayah merupakan zeolit bertipe mordenit, klinoptilolit, dan heulandit dengan fasa pengotor quartz. Luas permukaan zeolit alam Bayah lokasi 4 sebesar 46 m2/g. Model kesetimbangan yang sesuai untuk adsorpsi amonium oleh zeolit alam Bayah yaitu model Freundlich. Model kinetika adsorpsi yang paling sesuai untuk adsorpsi amonium oleh zeolit alam Bayah yaitu model kuasi orde satu. Kata Kunci: limbah rumah tangga, amonium, eutrofikasi, zeolit alam